Hubungan Australia dengan Indonesia faktor geografi, politik dan strategi keamanan Susan Critchley ; penerjemah, Sugiarta Sri Wibawa - Critchley, Susan; Sri Wibawa, Sugiarta (1995)
xiii, 238 hlm 23 cm